ANALISIS KONTRIBUSI DAN EFEKTIVITAS PAJAK HOTEL, PAJAK RESTORAN, DAN PAJAK PARKIR TERHADAP PENDAPATAN ASLI DAERAH (Studi Kasus Kota Surakarta dan Kota Yogyakarta tahun 2012-2018) - Prananda, Ismail Septin; Harimurti, Fadjar; Sunarti, Sunarti (Universitas Slamet Riyadi, 2020)
The research aims to determine the potential, effectiveness of local tax and its influence on regional indigenous revenue. The dependent variable used in this study is the indigenous revenue region. The independent variable is Hotel tax, restaurant tax and parking tax. The population in this research is the regional government Financial report (LKPD) taken from the regional Asset Financial Management Board (BPPKAD) of Surakarta and Yogyakarta city in 2012-2018. Samples in this study used census methods. The analysis used in this study was to use multiple linear regression. Based on the calculations can be said that, hotel tax in the city of Surakarta and Yogyakarta is very less contributing, besides the hotel tax in Surakarta and Yogyakarta City provides effectiveness to the local income. Based on the calculations it can be said that, the restaurant tax in Surakarta and Yogyakarta city is very less contributing, besides the Hotel tax in Surakarta and Yogyakarta city Provide effectiveness on regional income native. Based on the calculations can be said that, parking tax in the city of Surakarta and Yogyakarta city is very less than the contribution, besides the parking tax in Surakarta City and Yogyakarta City provide effectiveness to local income. Based on Hotel tax SPSS test results, restaurant taxes and parking taxes have a positive effect on the indigenous revenue.